Experimental Investigation of the Effects of Preheating on Still Productivity - Ridha Cherraye; Bachir Bouchekima (International Journal of Energetica)
Single basin solar still (SBSS) has low productivity in this experimental research, some techniques have been employed to solve this problem, these techniques consist of using a flat plate collector. The main aim of this research was to make efficient use of the flat plate collector (FPC) to increase solar still productivity, and it works as a hybrid device. The model solar water heater for the flat plat collector (FPC) was coupled with a solar still, and the tests were repeated in 3 to 5 winter days, and the results were measured in the same way for each day. The results revealed that the productivity of the still increased 87 % when coupled with one, and decreased 20 % and 50 % when coupled with two and three flat plate collectors in southern Algeria, respectively.